103k views
1 vote
Hello, help me please)

Hello, help me please)-example-1
User Babs
by
5.6k points

1 Answer

13 votes

Answer:

Given equation:


10^(5x-2)=2^(8x-3)

Take natural logs of both sides:


\implies \ln 10^(5x-2)= \ln 2^(8x-3)


\textsf{Apply log Power law}: \quad \ln_ax^n=n\ln_ax


\implies (5x-2)\ln 10=(8x-3) \ln 2

Expand brackets:


\implies 5x\ln 10 - 2\ln 10=8x \ln 2 -3 \ln 2

Collect like terms:


\implies 5x\ln 10 - 8x \ln 2 =2\ln 10-3 \ln 2

Factor left sides:


\implies x(5\ln 10 - 8 \ln 2) =2\ln 10-3 \ln 2


\textsf{Apply log Power law}: \quad \ln_ax^n=n\ln_ax


\implies x(\ln 10^5 - \ln 2^8) =\ln 10^2- \ln 2^3


\textsf{Apply log Quotient law}: \quad \ln_a(x)/(y)=\ln_ax - \ln_ay


\implies x\left(\ln\left((10^5)/(2^8)\right)\right) =\ln\left((10^2)/(2^3)\right)

Simplify:


\implies x\left(\ln\left((3125)/(8)\right)\right) =\ln\left((25)/(2)\right)


\implies x=(\ln\left((25)/(2)\right))/(\ln\left((3125)/(8)\right))


\implies x=0.4232297737...

User William Linton
by
6.3k points